The interplay between relative sea-level rise and sediment supply at the distal part of the Nile littoral cell. (February 2016) - Elyashiv, Hadar; Bookman, Revital; Zviely, Dov; Avnaim-Katav, Simona; Sandler, Amir; Sivan, Dorit
During Holocene sea-level rise, coastal areas became transitional environments as marine incursion covered the land. Changing conditions resulted in dynamic depositional environments that recorded the migration and stabilization of modern shorelines. These processes are viewed in the Zevulun Plain (Haifa Bay, Israel) record located in the northern edge of the Nile littoral cell. Sedimentological and palaeontological analyses combined with dating enabled the reconstruction of the Holocene chrono-stratigraphical frame. The results reveal an unconformity representing a long period of exposure and erosion during the last glacial. The interplay between relative sea-level rise and sediment supply was first set out by the deposition of alluvial sediments, evidence of the hydrological system reactivation and base level landward migration. Sea flooding of the Zevulun Plain started about 7.8 cal ka BP and the coastline was pushed eastward. Nile-driven sands transported by longshore currents formed dunes that blocked the rivers estuaries and led to wetlands formation. Peat accumulation is evident first in the north of the plain at 7.6–6.2 cal ka BP and later in the south at 6.5–5.5 cal ka BP. Both wetlands showed a change from fresh to brackish water environments at the end of their existence. Following the maximum sea-level rise and inland sea invasion at about 4 ka BP, alluvial sediments covered the plain and the coastline moved westward to its current position. This record serves as a model for the development of Mediterranean clastic coasts controlled by sea rise and infill processes.